Determination of β-Galactooligosaccharides by Liquid Chromatography. (26th February 2014) - Austin, Sean; Bénet, Thierry; Michaud, Julien; Cuany, Denis; Rohfritsch, Philippe
Abstract : Beta-galactooligosaccharides (GOS) are oligosaccharides normally produced industrially by transgalactosylation of lactose. They are also present naturally in the milk of many animals including humans and cows. GOS are thought to be good for health, being potential prebiotic fibres, and are increasingly added to food products. In order to control the GOS content of products, the AOAC official method 2001.02 was developed. However, the method has some shortcomings and in particular is unsuited to the analysis of products containing high levels of lactose such as infant formula. To overcome this problem, we developed a new method for application to infant formula and tested it on various GOS ingredients as well as infant formulae. When applied to GOS ingredients the results of the new method compare well with those of the official AOAC method, typically giving results in the range 90–110% of those of the official method and having an expanded measurement uncertainty of less than 15%. For three products, the results were outside this range (recoveries of 80–120% and expended measurement uncertainties up to 20%). When applied to the analysis of infant formula, recoveries were in the range of 92–102% and the expanded measurement uncertainties were between 4.2 and 11%.